自闭·不封闭 = Enclosed worlds, open minds. - Han, Weiding. (2010)
Autism is a mysterious neurological disorder that has no definitive cause and cure at present. Individuals with autism are typically perceived to be anti-social and do not enjoy the company of others. However, it is less known that such behaviour is the result of inborn social and communication impairment; being born with a disorder is not their choice. In fact, their inability to integrate into the society at times makes them helplessly think that they do not belong to this planet.